2012
DOI: 10.1037/a0025913
|View full text |Cite
|
Sign up to set email alerts
|

Early puzzle play: A predictor of preschoolers' spatial transformation skill.

Abstract: Individual differences in spatial skill emerge prior to kindergarten entry. However, little is known about the early experiences that may contribute to these differences. The current study examines the relation between children’s early puzzle play and their spatial skill. Children and parents (n = 53) were observed at home for 90 minutes every four months (six times) between 2 and 4 years of age (26 to 46 months). When children were 4 years 6 months old, they completed a spatial task involving mental transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
299
5
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(321 citation statements)
references
References 63 publications
10
299
5
7
Order By: Relevance
“…The idea of a close linkage between cognition and action or, in other words, between perceptual and motor systems of the brain, has recently gained new interest in the field of embodied cognition (Wilson, 2002;Zwaan, 1999). In support of this notion, recent evidence suggested that 4-year-olds' spatial transformation abilities were associated with how often they played with puzzles (Levine, Ratliff, Huttenlocher, & Cannon, 2011).…”
Section: Mental Object Rotation!and Motor Development In 8-and 10-monmentioning
confidence: 61%
“…The idea of a close linkage between cognition and action or, in other words, between perceptual and motor systems of the brain, has recently gained new interest in the field of embodied cognition (Wilson, 2002;Zwaan, 1999). In support of this notion, recent evidence suggested that 4-year-olds' spatial transformation abilities were associated with how often they played with puzzles (Levine, Ratliff, Huttenlocher, & Cannon, 2011).…”
Section: Mental Object Rotation!and Motor Development In 8-and 10-monmentioning
confidence: 61%
“…Together, these findings suggest that to effectively teach content from 2D materials and link it to information that children have already acquired from real-world experiences, teachers and parents should understand that there is a transfer deficit and be made aware of the educational implications. There are potential benefits to including media in the classroom, including enhanced engagement and interactivity, but additional scaffolding (Lauricella, Barr, & Calvert, 2009;Lauricella, Calvert, & Barr, 2014;Levine et al, 2012) by early educators may be necessary to facilitate transfer. Future research is necessary to assess how to facilitate transfer of learning between 2D media and 3D objects in the home and in the classroom.…”
Section: Practical Implications Of These Findings For Educational Setmentioning
confidence: 97%
“…The puzzle imitation task was chosen because it is nonverbal, which enables testing across a wider age range. It is also an ecologically valid imitation task because it involves an everyday activity (puzzle play) and because multiple early educational touchscreen applications use puzzles (Dickerson et al, 2013;Levine, Ratliff, Cannon, & Huttenlocher, 2012;Verdine, Golinkoff, Hirsh-Pasek, & Newcombe, 2014).…”
Section: The Current Studymentioning
confidence: 99%
“…Previous work (Levine, Ratliff, Huttenlocher, & Cannon, 2012) showed that puzzle play frequency, observed over the course of two years, was positively correlated to children's mental transformation performance at 4.5 years of age. More specifically, the quality of puzzle play (i.e., difficulty, level of engagement, and spatial language used in parent-child interactions) predicted girls' performance.…”
Section: Running Head: Mental Rotation In 3-to 5-year-olds 20mentioning
confidence: 99%